Perhitungan komputasi potensi Lawsone dan turunannya sebagai material aktif pada sel surya tersensitisasi zat warna - Mirella Fonda Maahury; Muhamad Abdulkadir Martoprawiro (JURNAL KIMIA MULAWARMAN, 2019)
Lawsone is a dye which found in henna plant. Computational calculations have been done for the lawsone and its derivatives. This computational calculation aims to obtain a stable optimized structure and electronic properties to predict potency of lawsone as a photosensitizer in dye sensitizer solar cell. Computational calculation were using DFT for geometry optimization ground state and TDDFT for single point calculation excitation state. Both state for calculation using B3LYP functional and 6-311G(d,p) as basis set. The calculation in gas phase. Geometry optimization obtain lawsone structure is planar. The present of functional methoxy and hydroxy causing decresing and increasing of bond length. Based on electronic properties, such as excitation energy, maximum absorption wavelength and percentage excitation, L0 has better potential as active material in dye sensitized solar cell.